ANALYSIS OF WELDED POLYPROPYLENE STRUCTURES: COMBINATION OF EXPERIMENTS AND SIMULATIONS - Theresa Distlbacher; Martin Reiter; Zoltan Major (Acta Polytechnica CTU Proceedings)
The effect of joining by extrusion welding on the tensional stiffness and strength of a Polypropylene copolymer was analysed. Short-term and creep tests with laboratory specimens were conducted. Welded joint sub-components were simulated with the finite element method and the results were validated by experiments.